Powering the Philippine Economy: Electricity, Economics and Policy - Ravago, Majah-Leah V (Archīum Ateneo, 2018)
Energy, in particular power development, is a challenging undertaking, one that requires thoughtful consideration of the economy and the environment. There are no hard and fast rules for achieving a cost-efficient, sustainable, and environmentally-sound energy sector. Thus, it is imperative to have evidence-based research studies to inform the most appropriate energy policies to support the aspirations of the Filipino people. Bringing energy and economic development to the forefront of public policy discussions is imperative. However, in the Philippines, few academic and policy programs exist in universities and economic centers to develop and promote knowledge, research, and best practices that can be used by policy makers, academics and others in designing and implementing economically-sound energy programs. Supported by a grant from the U.S. Agency for International Development, the Energy Policy and Development Program (EPDP) project was undertaken to help address this gap and provide an impetus towards the establishment of an independent think tank focused on energy policy research.